2012
DOI: 10.1111/j.1399-6576.2011.02630.x
|View full text |Cite
|
Sign up to set email alerts
|

Verification of endotracheal intubation in obese patients – temporal comparison of ultrasound vs. auscultation and capnography

Abstract: In obese patients, verification of endotracheal tube placement with US is as fast as auscultation alone and faster than the standard method of auscultation and capnography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 34 publications
0
18
2
Order By: Relevance
“…Similar conclusions were derived in obese patients also. [13] Anticipating thicker anterior chest wall in these patients and keeping the depth setting of the ultrasound machine at higher values from the beginning itself will facilitate faster identification of lung sliding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were derived in obese patients also. [13] Anticipating thicker anterior chest wall in these patients and keeping the depth setting of the ultrasound machine at higher values from the beginning itself will facilitate faster identification of lung sliding.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, Pfeiffer et al [24,25] documented that verification of ETT placement with US is as fast as auscultation alone and faster than the combination of auscultation and capnography, even in obese patients [23]. Thereafter, Alonso Quintela et al [9] reported despite US was slower than capnography for identifying ETT, US is as effective and quicker than X-ray for assessment of ETT insertion depth, and it may contribute to decrease the routine use of X-ray after tracheal intubation.…”
Section: Discussionmentioning
confidence: 56%
“…The use of a ‘Bougie’ to aid tube passage during surgical airway placement is also recommended, especially in situations of anticipated difficulty. When available and following requisite training, the use of ultrasound may assist in identifying anatomical landmarks, as well as correct tube placement18 19 [IIb].…”
Section: Methodsmentioning
confidence: 99%